Gut microbiota and bacterial associations in monkeys with gastrointestinal diseases in the setting of helminth infestation - V. A. Kalashnikova; T. P. Egorova; A. V. Demerchyan; V. I. Polyakova; Y. I. Lenshina; D. A. Ilyazyants; I. M. Arshba (Ветеринария сегодня)
One of the topical issues of current primatology is spontaneous pathology in monkeys, primarily gastrointestinal infections, which are the leading ones in the morbidity and mortality patterns of the animals raised in captivity. Gastrointestinal pathology in monkeys involves complicated infectious processes, most often of associative type, with the formation of various bacterial and parasitic associations. The study demonstrates the results of gastrointestinal disease and helminth infestation monitoring as well as of the microbial flora spectrum analysis in monkeys in 2017–2022. Mortality of monkeys due to gastrointestinal diseases in the specified period amounted to 60.5%. The postmortem study demonstrated that the leading position in this pathology pattern in monkeys was taken by gastroenterocolitis (62.5%), with dominated chronic atrophic gastroenterocolitis in the acute phase (53.9%). The analysis of the six-year trend in animal mortality showed that the percentage of gastrointestinal diseases remained approximately at the same level every year. Helminth infestations were detected in 22.0% of the diseased animals and in 30.2% of the dead ones. Trichocephalus trichiurus was found in 93.3% of the diseased and in 99.7% of the dead monkeys, Strongyloides sp. – in 12.2% of the diseased and in 3.3% of the dead animals. Helminths were detected as mono- and less often as mixed infestations. In the isolated microflora, the top position was taken by the representatives of genus Proteus. The percentage of pathogenic enterobacteria detections was low, and Shigella flexneri was the leader among them. In monkeys that died from gastrointestinal diseases without parasitic infestation, the pathogenic enterobacteria detection rate was 2 times higher than in the infested animals. The microorganisms were isolated as monocultures and in associations. The microorganisms were isolated as monocultures and in associations Proteus spp. were detected more often. Gastrointestinal diseases of helminth-bacterial etiology in monkeys require complex therapy of the animals.